Magnesium - dietary intake, supplement use and serum concentration in elite young German athletes - Braun, H.; Koehler, K.; Achtzehn, S.; Predel, G.; Thevis, M.; Mester, J. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Magnesium (Mg) plays an important role in many cellular processes. This might explain why Mg supplement use is still widespread in the athlete community (Braun et al., 2009), even though dietary magnesium intake seems adequate for most athletes. Since data for young athletes is rare, the aim of this study was to compare dietary Mg intake, Mg supplement use and serum Mg concentrations in young athletes. Methods Between January 2007 and October 2008, 306 athletes visited the German research centre of elite sports for a medical examination. Two hundred fifty athletes reported their dietary situation using a validated 7 d food & activity record. On the morning following the recording period fasting blood samples were taken. A questionnaire regarding the frequency of supplement use was provided in advance by mail. Complete data was available for 195 (age 16.3 ± 2.8 y, male n = 99, female n = 96) athletes. Results Sixty-five (33 %) athletes took magnesium as dietary supplement in the past 4 weeks before the medical examination. Mean dietary magnesium intake (without supplements) was higher in supplement users (SU: 567 ± 196 mg/day) compared to non-users (NU: 485 ± 204 mg/day) (p < 0.01). However, dietary Mg density was similar (SU: 206 ± 47 mg/1000 kcal; NU: 199 ± 61 mg/1000 kcal). Mean serum levels were 0.86 ± 0.07 mmol/l (SU) and 0.87 ± 0.08 mmol/l (NU) respectively. Additionally those who consumed Mg supplements on a daily basis did not have elevated serum Mg levels (n = 8; 0.87 ± 0.06 mmol/l). While energy intake was significantly correlated with Mg intake (r = 0.68, p < 0.001), we found no association between Mg intake and serum Mg (r = 0.02). Discussion In the present study, we found decreased serum magnesium concentrations only in a few cases. However, it seems that an optimal serum Mg concentration for (young) athletes has not been defined (Fogelholm 1995). Mean Mg dietary intake were above the German RDA and increased with energy intake. In agreement with others (Fogelholm et al., 1991) we found that Mg serum does not reflect dietary intake. Consistent with an earlier study (Weller et al., 1998) there were no differences in serum Mg between SU and NU. Based on the described findings it should be questioned why young athletes use Mg supplements. The benefits of those supplements seem to be lacking, while the risk of contaminated supplements should not be underestimated. References Braun H., Koehler K., Geyer H., Kleinert J., Mester J., Schaenzer W (2009). Int J Sp Nutr Exerc Met, 19(1), 97-109 Weller E., Bachert P., Meineck HM., Friedmann B., Bartsch P., Mairbaurl H (1998). Med Sci Sp Exc, 30(11), 1584-1591 Fogelholm M., Laakso L., Lehto J., Ruokonen I (1991). Nutrition Research 11, 1111-1118 Fogelholm M (1995). Int J Sp Nutr 5(4), 267-284